Photocatalytic Activity of Ag-TiO2 Composites Deposited by Photoreduction under UV Irradiation - Carlos Díaz-Uribe; Jose Viloria; Lorraine Cervantes; William Vallejo; Karen Navarro; Eduard Romero; Cesar Quiñones (International Journal of Photoenergy)
In this work, we synthesized Ag nanoparticles on TiO2 thin films deposited on soda lime glass substrates. Ag nanoparticles were synthesized by photoreduction under UV irradiation silver nitrate solution. X-ray diffraction, Raman spectroscopy, scanning electron microscopy (SEM), and X-ray photoelectron spectroscopy (XPS) measurements were used for physicochemical characterization. The structural study showed that all samples were polycrystalline, main phases were anatase and rutile, and no additional signals were detected after surface modification. Raman spectroscopy suggested that silver aggregates deposited on the TiO2 films could exhibit the surface plasmon resonance (SPR) phenomenon; XPS and SEM analysis confirmed TiO2 film morphological modification after photoreduction process. Photocatalytic degradation of methylene blue (MB) was studied under UV irradiation in aqueous solution, and, besides, pseudo-first-order model was used to obtain kinetic information about photocatalytic degradation. Results indicated that Ag-TiO2 showed an important increase in photocatalytic activity under UV (from 20% to 35%); finally, Ag-TiO2 thin films had kapp value 2.4 × 10−3 ± 0.003 min−1 of 1.8 times greater than the kapp value 1.3 × 10−4 ± 0.0004 min−1 of TiO2 thin films.